PENGGUNAAN FRACTAL PADA VISCOUS FINGERING - Sutadiwiria, Gunawan
Viscous fingering is a representation of an unstable displacement process form in which a more viscous fluid is displaced by a less viscous fluid. This phenomenon is commonly found in the enhanced oil production process which is usually performed to increased oil recovery (EOR). The presence of viscous fingering in the EOR process usually gives a poor sweep efficiency of the displacement. In this thesis, viscous fingering is modeled by using DLA model in which fractal dimension is included. Basically, this model is a random walk particle simulation at lattice where it grows particle aggregate. Using this model, the shape of finger growth caused by unfavorable mobility displacement process can be predicted and the sweep efficiency can then be determined at given value of mobility ratio. A relation between DLA mobility ratio (MDLA) and reservoir mobility ratio (M) has also been developed and represented in single form of equation. It also found that fractal dimension for two dimensional viscous fingering ranges from 1.67 to 1.99, depending on the value of MDLA. Using this model, determination of sweep efficiency and the shape of viscous finger, which is the main result of this study, can be improved.